Minhas memórias: meu caminho na formação de professora - AZEVEDO, Mariza de Lima (2023)
The main objective of this work is to record my life trajectory from childhood to the present day. The memorial is characterized as a research with a qualitative approach that has life history or (auto)biographical method as its method. The analysis of the research was based on the autobiography that expressed the “writing of life itself”. The data for the development of this study were collected from my personal file and from other sources of information, such as: the written source; the internet (scientific books and magazines) and the oral source: the data came from my own report. From the remembrance of my life, it is concluded that the knowledge and experiences acquired before, during and after this memorial served and will serve for the improvement and re-signification of my teaching practice, which will now be developed with more competences. It also reflects the knowledge construction process during the training and learning period